The Use of Personal Protective Equipment Compliance among Midwives During COVID-19 Pandemic in Indonesia - Nur Leli; Rini Kundaryanti; Shinta Novelia (Nursing and Health Sciences Journal (NHSJ), 2022)
Individuals most at risk of infection are those who are in close contact with COVID 19 patients, such as midwives who run Independent Practices. Midwives can protect themselves when providing care by complying with infection prevention and control practices that include proper administrative, environmental and engineering control and use of Personal Protective Equipment (PPE) (i.e. appropriate in the selection of the appropriate type of PPE, how it is used, how to release and how to dispose or wash PPE). So researchers are interested in researching the factors that affect the behavior of the use of PPE in health workers. This study aimed to analyze factors that can affect the behavior of PPE use among midwives. This type of research was observational analytical research methods. The population in this study was 87 midwives. The study was conducted in Sambas Regency in July-August 2021. This research instrument was a questionnaire. The results of the study showed there was relationship between knowledge (p-value 0.395), and education level (p-value 0.103) with compliance, there was a relationship of working life (p-value 0.000) and availability of PPE (p-value 0.001) With Compliance of Using Personal Protective Equipment (PPE) in Sambas Regency In 2021. It is expected to be the basis and guideline to conduct further research related to the behavior of using PPE while working on midwives in health care facilities in Indonesia.